Correction: Yao, Y., et al. Activation of Slit2/Robo1 Signaling Promotes Tumor Metastasis in Colorectal Carcinoma through Activation of the TGF-β/Smads Pathway. Cells 2019, 8, 635 - Yuying Yao; Zijun Zhou; Liuyou Li; Junchen Li; Lixun Huang; Jiangchao Li; Cuiling Qi; Lingyun Zheng; Lijing Wang; Qian-Qian Zhang (Cells, 2020)
The author wishes to make the following correction to this paper [...]